Review of Public and Private Disaster Risk Financing Mechanisms in Central Europe - Gurenko, Eugene N.; Dumitru, Denisa (World Bank, Washington, DC, 2013)
This study comprises a review of government post-disaster safety nets as well as those provided by the private insurance market in four countries of Central Europe, namely the Czech Republic, Hungary, Poland, and Slovakia. The study attempts to establish the extent of financial vulnerability of governments and households to natural hazards in four countries of Central Europe by examining: 1) the fiscal policy of four Central European countries in the areas of post-disaster relief and reconstruction; and 2) the extent of catastrophe insurance coverage provided by the private insurance industry in the region as well as the technical capacity of national insurance markets to manage catastrophe insurance risk. The study is intended for four principal audiences: government officials in Central European countries; World Bank staff involved in disaster risk financing and reconstruction projects; the international development community as well as the private insurance and reinsurance industry. This report was prepared based on a series of written surveys followed by interviews with key government officials, government experts and insurers in four countries of the study. The field work has been supplemented by a review of the pertinent literature. The structure of the report is as follows. chapter one reviews the level of catastrophe insurance penetration in the four countries of Central Europe. It also provides an overview of fiscal policies and mechanisms currently in place for dealing with national emergencies. Chapter two presents the main findings and policy recommendations of the study.